FRI0021 Weight Loss in Obese Rheumatoid Arthritis Patients Improves Disease Activity Without Modifying RA Treatment. (9th June 2015) - Gigante, M.R.; Gremese, E.; Tolusso, B.; Fedele, A.L.; Canestri, S.; Aquilanti, B.; Di Mario, C.; Petricca, L.; Alivernini, S.; Ferraccioli, G.
Abstract : Background: Obesity is one of the potentially preventable risk factors for RA being associated with RA onset, disease severity and poor response to therapy. New evidence suggests that weight loss may lead to outcome improvement in obese osteoarthritis and psoriatic arthritis patients. Objectives: To evaluate whether, in obese RA patients with a low-moderate disease activity, a weight loss obtained with a controlled nutritional intervention may lead to an improvement of disease activity and to a reduced need of increasing therapeutic regimens, without modifying RA treatment during the study period. Methods: 64 consecutive obese RA patients (BMI>30 kg/m 2 ) with DAS>1.6, treated according to a treat-to-target strategy and in a stable therapy with conventional DMARDs (cDMARDs) and/or biological DMARDs (bDMARDs) for at least 12 weeks, were enrolled. All patients underwent a scheduled diet under a Nutritionist guide, aimed at a weight loss >5% at 6 months (T6), maintaining unchanged the RA therapy. Patients were evaluated by rheumatologist and nutritionist every 2 months and at each visit clinical and laboratory data and the ACR/EULAR core data set was registered. Disease activity was evaluated by Disease Activity Score on 44 joints (DAS) and Simplified Disease Activity Index (SDAI). Results: Of the 64 RA patients (82.8% female, age 56.5±12.5 years, disease duration 8.1±8.1 years, 66.9% seropositive, baseline (T0) DAS 2.8±0.7, baseline BMI 35.3±4.3), 36 (56.3%) were under cDMARDs-only therapy and 28 (43.8%) under biologic bDMARDs therapy ± cDMARDs. At now, 56 patients reached the 6 months follow-up. At T6, the mean reduction in percentage of body weight was 6.6±5.5% and of DAS was 25.4±28.5% (DAS T6: 2.0±0.7, p<0.01 vs DAS T0). Moreover, at T6 patients showed a significant improvement of SDAI with respect to baseline (p<0.01), of tender (p<0.01) and swollen (p<0.01) joint count, of systemic inflammatory parameters (ESR p=0.001, CRP p=0.003), GH (p<0.01), VAS pain (p<0.01) and HAQ (p<0.01), without any change of RA therapy nor corticosteroids need. Dividing patients according to the percentage of weight loss at T6, the 34 (60.1%) RA patients reaching a weight reduction >5% of the baseline body weight obtained higher rates of DAS remission than patients with a weight reduction <5% (DAS remission at T6: 35.3% vs 13.6%, respectively, p=0.07), as well as of SDAI remission (33.3% vs 4.5%, p=0.02). The differences were even more significant when considering a weight reduction >10% (DAS remission at T6: 57.1% in patients reaching 10% weight reduction vs 16.7% in not reaching patients, p=0.01; SDAI remission at T6: 57.1% vs 9.8%, p=0.001). Results were similar between patients under cDMARDs-only and bDMARDs treatment. Conclusions: A weight loss obtained with a controlled diet in obese still active RA patients can allow to obtain a better disease control without changing the treatment of RA, and in particular a weight loss >10% permits to reach disease remission in a significant percentage of patients, and therefore reduces the need of an increase in therapy. The effects of weight loss based on a nutritional intervention, and so applicable at the population level, on the RA disease course appears to be crucial in terms of potential clinical and pharmacoeconomics perspectives. Disclosure of Interest: None declared